Response to bronchodilators assessed by lung mechanics. Issue 10 (October 1986) - Greenough, A; Loftus, B G; Pool, J; Price, J F
Abstract : Abnormalities of compliance and functional residual capacity were shown in eight young children aged 2-8 years with asthma during an acute attack. In a randomised, placebo controlled study treatment with bronchodilator (salbutamol) was associated with a significant improvement in compliance and lessening of hyperinflation as shown by a reduction in functional residual capacity.